Quantification of aluminum-induced changes in wheat root architecture by X-ray microcomputed tomography - Lazarević, Boris; Sturrock, Craig; Poljak, Milan; Mooney, Sacha J. (Taylor & Francis, 2016)
Root architectural traits are of fundamental importance for plant performance, especially under unfavorable soil conditions. This study examined the effect of aluminum (Al) toxicity in different growing media (nutrient solutions and soil) on root architecture of two wheat (Triticum aestivum L.) cultivars with different Al tolerances. Seedlings were grown in acidic and limed soil and in two contrasting nutrient solutions. Root systems of soil-grown plants were scanned using x-ray microcomputed tomography (µCT) while that of nutrient solution–grown plants were assesses using WinRhizo, 3 and 5 days after planting (DAP), respectively. Aluminum caused significant reduction of all examined root traits (number of seminal roots, root length, length of the longest seminal root, root surface area, and root volume). Growth in acidic soil caused significant reduction in root length, length of the longest seminal root, and root surface area at 5 DAP. Soil-grown plants produced a larger root system compared to plants grown in nutrient solutions. Aluminum toxicity–induced differences of root traits were also found between different nutrient solutions. Beside the well-known reduction of root length, Al toxicity had a profound effect on other root architectural traits. X-ray µCT has revealed root architectural changes under specific conditions of acidic, Al-toxic soil. Differences obtained in Al-induced effects on root architecture between different nutrient solutions as well as between different growing systems emphasize the need for further study of root architecture, especially under specific conditions of Al toxicity in acidic soils.